2016
DOI: 10.1109/tuffc.2016.2539323
|View full text |Cite|
|
Sign up to set email alerts
|

On the Quantitative Potential of Viscoelastic Response (VisR) Ultrasound Using the One-Dimensional Mass-Spring-Damper Model

Abstract: Viscoelastic Response (VisR) ultrasound is an acoustic radiation force (ARF)-based imaging method that fits induced displacements to a one-dimensional (1D) mass-spring-damper (MSD) model to estimate the ratio of viscous to elastic moduli, τ, in viscoelastic materials. Error in VisR τ estimation arises from inertia and acoustic displacement underestimation. These error sources are herein evaluated using finite element method (FEM) simulations, error correction methods are developed, and corrected VisR τ estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Viscoelastic response (VisR) ultrasound is an alternative ARF-based tool using two co-localized ARF impulses to delineate tissue properties by measuring viscosity and elasticity (for details, see [40]). Hossain et al performed a prospective study with 44 patients to examine the ability of VisR to evaluate renal transplant status.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Viscoelastic response (VisR) ultrasound is an alternative ARF-based tool using two co-localized ARF impulses to delineate tissue properties by measuring viscosity and elasticity (for details, see [40]). Hossain et al performed a prospective study with 44 patients to examine the ability of VisR to evaluate renal transplant status.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Voigt model has been shown to outperform the Maxwell model for the agar-gelatin phantom and bovine muscles [ 28 ]. The effect of inertia is neglected as other studies have shown that the percentage error in the estimated time constant after correction was only 10% [ 18 ]. Also due to the complexity of the three dimensional acoustic radiation force push, a correction function had to be derived empirically [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effect of inertia is neglected as other studies have shown that the percentage error in the estimated time constant after correction was only 10% [ 18 ]. Also due to the complexity of the three dimensional acoustic radiation force push, a correction function had to be derived empirically [ 18 ]. The Voigt model consists of a spring and dashpot in parallel, where spring represents the elastic part of the medium and the dashpot represents the viscous part.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the ratios of a given median VisR measure for all possible ROI combinations (for example, the ratio of τ in the oC to the cC, or the ratio of RE in the iC to the oP) were calculated. These ratio calculations were performed to control for subject-to-subject variations in VisR outcome metrics, which arise from variability in the ARF amplitude (Selzo et al, 2016; Zhao, 2013). Note that ARF amplitude varies with system power level, duration of the ARF excitation, focal depth, tissue attenuation, and phase aberration.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative ARF-based approach to interrogating the elastic and viscous properties of tissue is Viscoelastic Response (VisR) ultrasound, which is described in detail in: (Selzo et al, 2016; Selzo and Gallippi, 2013). Briefly, VisR is performed using two co-localized ARF impulses that are separated by < 1 ms in time.…”
Section: Introductionmentioning
confidence: 99%